Computational study of binding of oseltamivir to neuraminidase mutants of influenza A virus - Muhammad Arba, Sri Wahyuli, Setyanto Tri Wahyudi, Amir Karton, Chun Wu (Journal of Applied Pharmaceutical Science, 2024)
Oseltamivir (OTV), which targets the neuraminidase (NA) of the Influenza A virus (IAV), has been reported to develop resistance. Here, we performed a computational study on the binding modes of OTV in the wild-type and popular mutants of IAV NA (E119A, E119D, E119G, H274Y, I117T, I117V, I117V-E119A, K150N, N294S, R292K, V116A, and Y252H). The Arg118, Glu119, Asp151, Arg152, Glu276, Arg292, and Arg371 were identified as crucial interacting residues with the drug. The energy decomposition analysis showed that with few exceptions, the dispersion interaction is the dominant interaction, followed by the charge-transfer and polarization interactions. The affinities for OTV were greatly reduced in all mutant systems, particularly in R292K and Y252H. The present study may be substantial in the design of new OTV analogues with better affinities to overcome the present drug resistance.
Keywords: Influenza A virus, oseltamivir resistance, neuraminidase, MD simulation, protein mutation